Barriers to breast self examination practice among Malaysian female students: a cross sectional study - Akhtari-Zavare, Mehrnoosh; Juni, Muhamad Hanafiah; Ismail, Irmi Zarina; Md Said, Salmiah; Abdul Latiff, Latiffah (SpringerOpen, 2015)
Introduction: Breast cancer is the most frequent cancer and the second reason of cancer deaths among woman worldwide, including Malaysia. The objective of this paper is to assess the practice of breast self-examination (BSE) and identify the barriers of BSE practice among undergraduate female students in Malaysia. Methods: A cross-sectional study conducted among 810 female undergraduate students in Klang Valley, Malaysia between April–Jun 2012. Data was collected via self-administered questionnaire which was developed and pre-tested for this study. Results: The majority of respondents were Malay 709 (95.6 %) and single 719 (96.9 %) with a mean age of 21.7 (1.1). Only hundred eleven (15 %) of the participants had a family history of breast cancer. 70.5 % of the respondents do not practice breast self-examination, 70.5 % do not know how to do it, 64.7 and 61.5 % reported no symptoms of breast cancer and worries to detect breast cancer, respectively. Univariate analysis showed that age, marital status and personal history of breast disease were statistically associated with the practice of breast self-examination. Conclusion: In this study, a high percentage of respondents were aware of breast cancer but do not perform breast self-examination. Knowledge, socio-cultural and environmental factors were identified as barriers; so it is recommended that knowledge among the public about breast cancer and promotion of public breast health awareness campaigns through the media should be carried out.